Female meiosis II and pronuclear fusion require the microtubule transport factor Bicaudal D. - Vazquez-Pianzola, P.; Beuchle, D.; Saro, G.; Hernández, G.; Maldonado, G.; Brunßen, D.; Meister, P.; Suter, B. (Development, 2022)
Bicaudal D (BicD) is a dynein adaptor that transports different cargoes along microtubules. Reducing the activity of BicD specifically in freshly laid Drosophila eggs by acute protein degradation revealed that BicD is needed to produce normal female meiosis II products, to prevent female meiotic products from re-entering the cell cycle, and for pronuclear fusion. Given that BicD is required to localize the spindle assembly checkpoint (SAC) components Mad2 and BubR1 to the female meiotic products, it appears that BicD functions to localize these components to control metaphase arrest of polar bodies. BicD interacts with Clathrin heavy chain (Chc), and both proteins localize to centrosomes, mitotic spindles and the tandem spindles during female meiosis II. Furthermore, BicD is required to localize clathrin and the microtubule-stabilizing factors transforming acidic coiled-coil protein (D-TACC/Tacc) and Mini spindles (Msps) correctly to the meiosis II spindles, suggesting that failure to localize these proteins may perturb SAC function. Furthermore, immediately after the establishment of the female pronucleus, D-TACC and Caenorhabditis elegans BicD, tacc and Chc are also needed for pronuclear fusion, suggesting that the underlying mechanism might be more widely used across species.